If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + 5 = 7 Reorder the terms: 5 + Z = 7 Solving 5 + Z = 7 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + Z = 7 + -5 Combine like terms: 5 + -5 = 0 0 + Z = 7 + -5 Z = 7 + -5 Combine like terms: 7 + -5 = 2 Z = 2 Simplifying Z = 2
| 2a+3=3a+2 | | 2/3x−5=1/2x−3. | | 8-7(-5+x)-2x= | | 1/2m+2/3≤2/3m+2. | | tanx=.1875 | | p-7=13 | | 24x^2-28x=0 | | S+3=4 | | x-y=310 | | x^2+77.20715x-5578.344647062639=0 | | 3.25+6.2(4.83+7.12)= | | x-3/22=0 | | 3x+5=-61 | | X-6=50whatisx | | 30+x=12 | | 11+13=3x | | X+(.09)x=30 | | 20-((4/5)x)= | | -2.2x(-2)-(-1/4)x5 | | 20-4/5*X= | | 15-14=22 | | 1.00+3.00x=3.00+2.00x | | 20-4/5*x=16 | | 10+12=28 | | 3x^2-7x+1=19 | | 20-((4/5)*X)=16 | | 42-5x= | | 5+3r=5r-18 | | -5=1/2(x+4)-3/2x | | f(x)=x^2+6ix-3ix^2-2x+45i-15 | | 2(4p-9)-10=-36+8p | | -3+-4+9n=2 |